Características del retiro del mercado de productos farmacéuticos, dispositivos médicos y productos sanitarios en un establecimiento Farmacéutico de Trujillo - Alonzo Aguirre, Diana Nataly (2017)
The present research aims to describe the characteristics of the withdrawal of the market of pharmaceutical products, medical devices and sanitary products in a Pharmaceutical Establishment of Trujillo. It is a descriptive, transversal and retrospective research. It consisted of the immobilization and withdrawal of 11 pharmaceutical products from 4 Laboratories. Of which the following results were obtained: Eurofarma, with 4 immobilized products; AMLOCAR 5 mg tablet, with 2906 units collected; Followed by Markos with its product UROBAC FORTE Cja x 200 tablets, with 23256 units collected, Medifarma with the product GASEOVET chewable tablet, with 1369 units collected and finally the laboratory Roemmers with its product OVUDATE Cja x 60 ova, during the period 2016. Concluding that the highest percentage of immobilizations and withdrawals of pharmaceutical products is due to the voluntary suspension of their distribution